OMBUDSMAN OF THE REPUBLIC OF INDONESIA SUPERVISION OF NOTARY SUPERVISORY COUNCIL - Harahap, Meilisa Fitri; Efendi, Roni (Nurani, 2020)
Notary Supervisory Council (MPN), which is suspected of having maladministration in the form of lengthy delays in the rapporteur's certainty about his report to the notary, so that the rapporteur reports to the Ombudsman. The Ombudsman, as a government agency for civil servants, has the power to monitor service providers, including those provided by the Notary Board (MPN). The urgency of this research is to review the legality of the Ombudsman in overseeing the MPI. This research is normative and empirical legal research that uses qualitative analysis. This research shows that the MPN is authorized to supervise and supervise notaries in the provision of public services in the form of administrative services and services, so that the MPN is under the Ombudsman's supervision. The Ombudsman's completion of reports of alleged maladministration by the MPN relies on public reports and then follows them up according to the Ombudsman's authority. The Ombudsman examined and followed up the report so that the MPP immediately forwarded the decision to the notary with a written warning. Key words: Supervision, Ombudsman, the Brethren of the notary